1994
DOI: 10.1002/ajh.2830460414
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor in plasma of patients with disseminated intravascular coagulation

Abstract: Recently it has been shown that tissue factor (TF), an important trigger for initiating blood coagulation, is present in the circulating plasma. In order to assess the clinical implications of TF in plasma, plasma concentration of TF was quantitated in 65 patients with disseminated intravascular coagulation (DIC). The mean concentration of plasma TF was elevated in patients with DIC at presentation as compared with healthy subjects (446 +/- SD 536 pg/ml vs. 138 +/- 51 pg/ml, P < 0.001). Abnormally high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
5
27
2
Order By: Relevance
“…Plasma TF concentration has been reported to be increased in various disease such as disseminated intravascular coagulation (DIC), ischaemic heart disease, antiphospholipid syndrome, and cancer (Koyama et al, 1994;Takahashi et al, 1994;Wada et al, 1994;Suefuji et al, 1997;Cuadrando et al, 1998;Falciani et al, 1998;Misumi et al, 1998). We showed that plasma TF concentration was up-regulated in primary and recurrent breast cancer patients.…”
Section: supporting
confidence: 53%
“…Plasma TF concentration has been reported to be increased in various disease such as disseminated intravascular coagulation (DIC), ischaemic heart disease, antiphospholipid syndrome, and cancer (Koyama et al, 1994;Takahashi et al, 1994;Wada et al, 1994;Suefuji et al, 1997;Cuadrando et al, 1998;Falciani et al, 1998;Misumi et al, 1998). We showed that plasma TF concentration was up-regulated in primary and recurrent breast cancer patients.…”
Section: supporting
confidence: 53%
“…These studies demonstrated a 2-to 3-fold faster clotting time when adipose tissue extracts from obese mice were compared with those from the lean mice (data not shown). Finally, hypercoagulable states caused by shedding of TF-rich microvesicles from cell surfaces have been demonstrated in cancer (52), dessimionated intravascular coagulation (53,54), collagen disease, diabetic microangiopathy, and chronic renal failure (55). Plasma TF activity was also observed in diabetes mellitus patients, with the concentrations being significantly higher in patients with retinopathy or nephropathy than in patients with no complications (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, controversy has emerged concerning the presence and functionality of TF species circulating in blood. Reports of circulating TF can be divided into those showing TF localized on the surface of blood cells and microparticles and those describing a TF species that circulates as a soluble protein (21)(22)(23)(24)(25)(26)(27). These blood TF species are invoked in support of a new hypothesis that TF-dependent thrombin generation requires a continuous infusion of this cofactor.…”
Section: Tissue Factor (Tf)mentioning
confidence: 99%